Immunological Aspects of Dental Implant Rejection. (9th December 2020) - Baseri, Milad; Radmand, Faraz; Hamedi, Reyhaneh; Yousefi, Mehdi; Kafil, Hossein Samadi
Abstract : Nowadays, dental implants are a prominent therapeutic approach among dentists for replacing missing teeth. Failure in dental implants is a severe challenge recently. The factors which lead to dental implant failure are known. These factors can be categorized into different groups. In this article, we discussed the immunological aspects of implant failure as one of these groups. Cytokines and immune cells have extensive and various functions in peri-implantitis. The equilibrium between pro and anti-inflammatory cytokines and cells, which involve in this orchestra, has a crucial role in implant prognosis. In conclusion, immune cells, especially macrophages and dendritic cells, almost increased in the patients with implant failure. Also, proinflammatory cytokines were proposed as diagnostic factors according to their higher levels in dental implant rejection.